Precisión de los índices estadísticas: Técnicas de jacknife & bootstrap = Precision of statistical indices: Jacknife &bootstrap techniques. - Badii Zabeh, Mohammad Hosein; Castillo, J.; Wong, A.; Landeros, J. (Universidad Autónoma de Nuevo León, 2007)
Abstract. The processes involved in jacknife and bootstrap techniques are described. The relevance of these techniques as the means of estimating the degree of sampling precision is explained.